In Vitro Antioxidant Activity of Chrysanthemum indicum Flowers Extract and Its Fraction - Dolongtelide, Jeclin Inebel; Fatimawali, Fatimawali; Tallei, Trina Ekawati; Suoth, Elly Juliana; Simbala, Herny Emma Inonta; Antasionasti, Irma; Kalalo, Marko Jeremia (Heca Sentra Analitika, 2023)
Chrysanthemum indicum L., commonly known as Chrysanthemum flower, is an herbaceous plant that has a long-established history of medicinal usage. There has been extensive research about C. indicium L, especially about its antioxidant activities, but not much has been done on its fraction. This study aimed to explore the efficacy of the ethanol extract and its fraction derived from Chrysanthemum flowers in scavenging free radicals. The antioxidant potential of the ethanol extract, as well as its aqueous and n-hexane fractions, was evaluated using the 2,2-diphenyl-1-picrilhidrazine (DPPH) method in vitro. The degree of antioxidant activity was quantified by determining the IC50 value, which corresponds to the concentration of the extract or fractions required to inhibit 50% of DPPH free radicals. The results obtained from this investigation provide strong evidence that the ethanolic extract, as well as its aqueous and n-hexane fractions, exhibited significant antioxidant activity. The measured IC50 values for the ethanolic extract, aqueous fraction, and n-hexane fraction were 1.350 µg/mL, 1.109 µg/mL, and 7.588 µg/mL, respectively.